Bioactivity of Wild and Cultivated Legumes: Phytochemical Content and Antioxidant Properties - Eleni D. Myrtsi; Epameinondas Evergetis; Sofia D. Koulocheri; Serkos A. Haroutounian (Antioxidants, 2023)
The global demand for increased meat production has brought to the surface several obstacles concerning environmental impacts, animals’ welfare, and quality features, revealing the need to produce safe foodstuffs with an environmentally acceptable procedure. In this regard, the incorporation of legumes into animal diets constitutes a sustainable way out that prevents these apprehensions. Legumes are plant crops belonging to the Fabaceae family and are known for their rich content of secondary metabolites., displaying significant antioxidant properties and a series of health and environmental benefits. The study herein aims to investigate the chemical composition and antioxidant activities of indigenous and cultivated legume plants used for food and feed. The respective results indicate that the methanolic extract of Lathyrus laxiflorus (Desf.) Kuntze displayed the highest phenolic (64.8 mg gallic acid equivalents/g extract) and tannin (419.6 mg catechin equivalents/g extract) content, while the dichloromethane extract of Astragalus glycyphyllos L., Trifolium physodes Steven ex M.Bieb. and Bituminaria bituminosa (L.) C.H.Stirt. plant samples exhibited the richest content in carotenoids lutein (0.0431 mg/g A. glycyphyllos extract and 0.0546 mg/g B. bituminosa extract), α-carotene (0.0431 mg/g T. physodes extract) and β-carotene (0.090 mg/g T. physodes extract and 0.3705 mg/g B. bituminosa extract) establishing their potential role as vitamin A precursor sources. Results presented herein verify the great potential of Fabaceae family plants for utilization as pasture plants and/or dietary ingredients, since their cultivation has a positive impact on the environment, and they were found to contain essential nutrients capable to improve health, welfare, and safety.